Matrix Metalloproteinase 2 and 9 Enzymatic Activities are Selectively Increased in the Myocardium of Chronic Chagas Disease Cardiomyopathy Patients: Role of TIMPs - Baron, Monique Andrade; Ferreira, Ludmila Rodrigues Pinto; Teixeira, Priscila Camillo; Moretti, Ana Iochabel Soares; Santos, Ronaldo Honorato Barros; Frade, Amanda Farage; Kuramoto, Andréia; Debbas, Victor; Benvenuti, Luiz Alberto; Gaiotto, Fabio Antônio; Bacal, Fernando; Pomerantzeff, Pablo; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Chronic Chagas disease (CCC) is an inflammatory dilated cardiomyopathy with a worse prognosis compared to other cardiomyopathies. We show the expression and activity of Matrix Metalloproteinases (MMP) and of their inhibitors TIMP (tissue inhibitor of metalloproteinases) in myocardial samples of end stage CCC, idiopathic dilated cardiomyopathy (DCM) patients, and from organ donors. Our results showed significantly increased mRNA expression of several MMPs, several TIMPs and EMMPRIN in CCC and DCM samples. MMP-2 and TIMP-2 protein levels were significantly elevated in both sample groups, while MMP-9 protein level was exclusively increased in CCC. MMPs 2 and 9 activities were also exclusively increased in CCC. Results suggest that the balance between proteins that inhibit the MMP-2 and 9 is shifted toward their activation. Inflammation-induced increases in MMP-2 and 9 activity and expression associated with imbalanced TIMP regulation could be related to a more extensive heart remodeling and poorer prognosis in CCC patients.